Report on the 12th Conference of the Groupe des Cartothécaires de LIBER, 27 June – 1 July 2000, København, Denmark - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
This was another stimulating and enjoyable conference of the Groupe des Cartothécaires held in the impressive gravity-defying new extension to the Kongelige Bibliotek. The papers and issues discussed ranged from the everyday and practical to the abstract and theoretical, from historical cartography to future digital glints in the eye, and this report is inevitably a personal and simplified account of the meeting. The intention is to summarize the main issues of the various papers, highlight general trends and provide a briefer introduction to papers, to which readers are referred for more information.